Internal Jugular Vein Thrombosis After Microwave Ablation of Cervical Lymph Node Metastasis in Papillary Thyroid Microcarcinoma: A Case Report - Liu, Ying; Wang, Xi-Ju; Wang, Jin-Ling; Liu, Li-Hong; Zhao, Shuo-Ran; Yu, Shou-Jun; Yang, Bei-Bei; Xu, Qing-Ling; Li, Jin-Ke; Wang, Shu-Rong (Frontiers in Endocrinology, 2022)
In this study, two patients with papillary thyroid carcinoma and lymph node metastasis were treated by Dr. Shurong Wang’s team and are reported. The two patients refused surgery and underwent microwave ablation (MWA) of the thyroid and lymph node lesions. Ultrasound review 2 days after MWA revealed internal jugular vein thrombosis. Patient #1 received low molecular weight heparin calcium injection, Xueshuantong injection, Xiangdan injection, and rivaroxaban. Patient #2 was treated with enoxaparin sodium injection, Xueshuantong injection, urokinase, and warfarin sodium tablet. The thrombus was successfully managed in each patient using anticoagulant treatment. Such complication of MWA has not been reported in many cases before. According to the relevant literature, thrombosis after thyroid cancer ablation might be related to subclinical hypothyroidism, increased heme oxidase 1 (HO-1) levels in the blood of patients with papillary thyroid cancer, and increased platelet content and mean platelet volume in patients with thyroid cancer. No specific cause of thrombosis was identified in the two cases reported here. No recurrence was observed after 1 (patient #1) and 4 (#2) years of follow-up. In conclusion, patients with papillary thyroid carcinoma and lymph node metastasis should undergo color Doppler ultrasound of the neck after MWA of thyroid lesions and neck metastasis.